Pembinaan Akhlak dan Hukum Islam Normatif dalam Pendidikan Agama Islam: Survei Preferensi Mahasiswa di Universitas Negeri Surabaya - Roihana Waliyyul Mursyidah; Feri Abdur Rokhman; Ahmad Mumtazus Tsaqofi (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
This study investigates students' preferences regarding moral development and normative Islamic law within the Islamic Religious Education curriculum at Universitas Negeri Surabaya, Indonesia, and explores their implications for curriculum development in public higher education. Employing a quantitative survey design, data were collected from 139 students enrolled in the compulsory Islamic Religious Education course through a structured questionnaire and analyzed using descriptive statistics to examine students' perceptions of the importance, satisfaction, and future needs related to both domains of learning. The findings indicate that students perceive moral development and normative Islamic law as equally essential components of Islamic Religious Education. Although students expressed balanced levels of satisfaction with both domains, many emphasized the need for greater reinforcement of contextual fiqh and the practical application of Islamic legal principles in everyday life. These findings suggest that moral education and normative Islamic law should not be positioned as competing curricular orientations but should instead be integrated proportionally to strengthen students' religious literacy, ethical reasoning, and contextual understanding of Islam. The study contributes empirical evidence supporting a more balanced and integrative approach to Islamic Religious Education curriculum development in Indonesian public universities.